Analisis Strategi Perencanaan Tenaga Kerja Untuk Meningkatkan Produktivitas Kerja (Studi Kasus Pada PT Adira Dinamika Multi Finance Tbk Cabang Cimahi) - Sarah Sarah; Rahma Afanezha Pasa Fadillah; Sayla Salsadila; Seni Ramadani; Syinta Dewi Nurfauziah; Resya Dwi Marselina (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze workforce planning strategies and their contribution to improving employee productivity at PT Adira Dinamika Multi Finance Tbk Cimahi Branch. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive analysis model. The findings indicate that workforce planning is carried out systematically by considering business targets, workload, employee turnover, and human resource competencies. Competency-based employee placement and development programs through training and job mentoring were found to support improved employee performance. Factors supporting the effectiveness of workforce planning include effective internal communication, work discipline, motivation, leadership, and a conducive work environment. Meanwhile, workload fluctuations and limited planning flexibility were identified as inhibiting factors. The study concludes that integrated and adaptive workforce planning plays a significant role in enhancing employee productivity and supporting the sustainable achievement of organizational goals.